AKTIVITAS SEHARI-HARI YANG MENDUKUNG PERKEMBANGAN ANAK TUNAGRAHITA RINGAN DI YAYASAN GRAHA CAHAYA - Siti Aisyah Saragih; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Mental retardation is a term that describes a person's intellectual limitations. This condition is generally detected in childhood, but can also appear in adulthood. Please note that this condition is no longer referred to as mental retardation. This research aims to determine the facilities and learning activities available at the Graha Cahaya Medika Foundation in Serang. This research method uses qualitative with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is triangulation. From the results of the research and observations I made on this child named Sulaiman, he was a mildly mentally retarded child. When he first met Sulaiman he was a quiet child with people he had just seen. After a humiliating approach with the supervision and help of the mother's nurse, Sulaiman finally started to get used to my presence. Sulaiman had difficulty speaking so I needed a nurse's translation so that I didn't mishear what Sulaiman was saying